5x-1+-2x+7=9

Simple and best practice solution for 5x-1+-2x+7=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-1+-2x+7=9 equation:


Simplifying
5x + -1 + -2x + 7 = 9

Reorder the terms:
-1 + 7 + 5x + -2x = 9

Combine like terms: -1 + 7 = 6
6 + 5x + -2x = 9

Combine like terms: 5x + -2x = 3x
6 + 3x = 9

Solving
6 + 3x = 9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 3x = 9 + -6

Combine like terms: 6 + -6 = 0
0 + 3x = 9 + -6
3x = 9 + -6

Combine like terms: 9 + -6 = 3
3x = 3

Divide each side by '3'.
x = 1

Simplifying
x = 1

See similar equations:

| 65-98+(85-6x)=9 | | (9x^3-4x^2+3x)-(7x^2+2x+4)= | | 3x/4-21x/32=9/8 | | 12.4=9+t | | -2(2)+9=-(-4)-3 | | 4(y-1/2)=y-6(5-Y) | | 3x/4-21x/32=-11/8 | | 4=-5/x-6 | | 10x+28=4x+178 | | (9b-5)-4(2b+2)=-3 | | 4x-8=-11 | | -5(3)+15=-10(3) | | 5z+5=5z+5 | | 185-6x=30x+17 | | -5(-1)+15=-10(1) | | 9+2z-8=9z+3-5z | | 2x-1=9x+78 | | 3(x+9)=7(x-23) | | 18a+31b+14a-2b= | | -5(2)+15=-10(7) | | x+2+x=-2 | | 6x-1(5x+5)=-8-2(x+12) | | 7-1/3 | | 6*9=n | | 6*8=n | | 5/4x-5/6x | | 3x+3=23-7x | | 3x+1/2(4x+8) | | 16x-6x-2x=0 | | 12(0)-6(3)=-18 | | 2x+(-2)*y=12 | | A*a=B*b |

Equations solver categories